University gatekeepers' use of the rhetoric of citizenship to relegate the status of students with disabilities in Canada. Issue 1 (2nd January 2019) - Easterbrook, Adam; Bulk, Laura Yvonne; Jarus, Tal; Hahn, Brian; Ghanouni, Parisa; Lee, Michael; Groening, Marlee; Opini, Bathseba; Parhar, Gurdeep
Abstract: Despite affirmation that students with disabilities should have equal access to education, individuals with disabilities are still not participating to the same degree as individuals without disabilities, particularly within postsecondary institutions. Students in Health and Human Service (HHS) programs experience many unique challenges and disadvantages. In-depth focus groups and interviews were conducted with 14 university stakeholders in HHS programs regarding their perceptions and experiences of working with students with disabilities. We found that the rhetoric of citizenship, specifically notions of rationality, autonomy, and productivity, interacts with beliefs about students with disabilities to allow stakeholders to justify their exclusion or limited participation. Our findings demonstrate how taken-for-granted beliefs can limit the inclusion of students with disabilities in ways that seem natural and unproblematic.